Urban rural differentials in spatial distribution of pregnant women having received Tetanus Toxoid injection by district in Punjab: Results from Pakistan Social and Living Standards Measurements Survey 2014-15 - Masood Ali Shaikh (Journal of the Pakistan Medical Association, 2022)
Dear Madam, Tetanus is a potentially fatal infection caused by Clostridium tetani bacteria, and during childbirth it can infect wounds and results in maternal death.1,2 Tetanus Toxoid (TT) vaccination is a simple, effective and freely available preventive measure available in public sector health facilities in Pakistan for pregnant women that can protect pregnant women and their newborns. Globally, TT vaccination is a standard preventive tool in the arsenal of primary health care service providers. In this study, district level TT vaccination coverage in pregnant women during their last pregnancy, in the Punjab province was mapped using Geographic information Systems to highlight its spatial distribution disaggregated by urban, rural residency status and the differences between the two types of dwellers. Continue...